Analisis Faktor-Faktor Yang Mempengaruhi Repurchase Intention Pada Produk Alat Berat - Rizky Putra; Berma Sakti Pradipta (CV. Multi Kreasi Media, 2022)
The purpose of this study is to examine a number of factors that are considered to influence repurchase intention, including customer satisfaction, brand awareness, product quality and brand loyalty. The literature used in this study includes brand image, price fairness, customer satisfaction, brand awareness and brand loyalty. This research method refers to a quantitative approach, which is more precisely a structural model. The results of this research study indicate that all factors affect repurchase intention in heavy equipment products.